STEM on Science Learning in Indonesia: An Opportunity and A Challenge - Muhammad Reyza Arief Taqwa; Abd Aziz Ardiansyah; Muhammad Agni Nurhidayat (Universitas Pendidikan Ganesha, 2020)
STEM has become a strategic issue in learning on an international scale, as well as in Indonesia. Related to the term